Assessment of the quantitative accuracy of Rietveld/XRD analysis of crystalline and amorphous phases in fly ash. Issue 16 (6th April 2017) - Zhao, Piqi; Liu, Xianping; De La Torre, A. G.; Lu, Lingchao; Sobolev, Konstantin
Abstract : A revised equation for amorphous based on internal standards is proposed. Abstract : An internal standard method based on Rietveld/XRD whole-pattern fitting analysis of fly ash is used to assess the quantitative accuracy to determine its crystalline and amorphous phases under various conditions such as internal standards (types, SiO2 or Al2 O3 and dosages, 10–50%), incident X-rays (laboratory or synchrotron) and refinement software (GSAS or TOPAS). The results reveal that the quantitative stability is quite sensible to minor phases, identical to the internal standard, in fly ash. Errors positively correlate with the weight fraction of that minor phase and negatively correlate with the dosage of an internal standard and amorphous phase content in fly ash. The original equation for the amorphous phase calculation is not applicable for a case with a higher inherent quartz content (>2.5%) in fly ash while the dosages of the internal standard is lower than 20%. The original equation is modified as proposed. Based on it, the quantitative results of five different patterns report a good reproducibility with the arithmetic mean errors and the standard errors of identified main phases of around 1%.